Transformasi Kewirausahaan dalam Era QRIS: Dinamika dan Solusi Sistem Pembayaran Nirkontan dari Perspektif Pedagang - Yadi, Agni Prajna; Hartanto, Arif Dwi; Ayatillah, Much Samsya; Wicaksono, Feri Nanang (Jurnal Informatika Ekonomi Bisnis, 2023)
The objectives of this study are to examine how technology acceptance factors (perceived ease of use, perceived usefulness, perceived security, subjective norms, and perceived compatibility) influence the intention of business owners/managers to adopt QRIS. Convenience sampling method was used for this survey. Data from 160 respondents were collected through a structured questionnaire measured with a Likert scale ranging from 1-7. An online-based web survey was utilized to reach the target respondents. Data were processed with SmartPLS and statistically tested with Structural Equation Modeling (SEM). The results indicate that perceived usefulness is the most important predictor of the intention to use QRIS. Additionally, a reasonably good predictive performance of the model is found. This research contributes to a more holistic understanding of the adoption of QRIS payment systems and provides insights that companies/merchant can leverage through the use of this payment technology. Significant implications for the development and refinement of QRIS. Developing a research model regarding subjective norms, perceived compatibility, perceived security, perceived ease of use, and perceived usefulness, including their roles in using QRIS. Helps explain the direct and indirect relationships in QRIS usage.